Bulk superconductivity in single‐phase Bi3O2S3. Issue 10 (19th July 2014) - Shao, Jifeng; Liu, Zhongheng; Yao, Xiong; Pi, Li; Tan, Shun; Zhang, Changjin; Zhang, Yuheng
<x xml:space="preserve">Abstract</x> We report the synthesis of single‐phase Bi3O2S3 sample and confirm the occurrence of bulk superconductivity with transition temperature at 5.8 K. The Bi3O2S3 superconductor is categorized as typical type‐II superconductor based on the results of both temperature and magnetic field dependences of magnetization. Hall coefficient measurements give evidence of a multiband character, with a dominant conduction mainly by electron‐like charge carriers. The charge carrier density is about 1.45 × 1019 cm–3, suggesting that the system has very low charge carrier density. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text> (© 2014 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim)